Numerical Simulations on the Extinguishing Effect of Water Mist System with Different Parameters of Longitudinal Ventilation in Curve Tunnel Fire - Zhizhong Liu; Chen Chen; Mu Liu; Song Wang; Yuzhu Liu (Advances in Civil Engineering)
Once a fire occurs in a long curve tunnel, the mixing of hot smoke flow and cold air leads to turbulence due to the curvature’s impact. This phenomenon results in a greater thermal pressure difference at the fire source and a substantially greater temperature field than in the straight tunnel. The longitudinal air flowing along the wall loses a lot of velocity in the curve tunnel due to the massive wall friction. Under the same fire extinguishing conditions, the curve tunnel and straight tunnel have different requirements for longitudinal ventilation. Factors such as tunnel curvature, longitudinal ventilation operation time, and ventilation velocity were all evaluated in order to investigate the influence of longitudinal ventilation parameters on the fire extinguishing effect of water mist in the curve tunnel. The fire extinguishing effect of water mist coupling with longitudinal ventilation in the curve tunnel is studied by numerical simulation, and the recommended values of ventilation operation time and ventilation velocity in the curve tunnel with the participation of the water mist system are given. The results show that (1) the fire extinguishing effect of water mist decreases with the increase of curvature under longitudinal ventilation and (2) fire prevention effect is best when water mist and longitudinal ventilation are used in the curved tunnel, and the ventilation velocity should be greater than 2 m/s.